Estetika Bunyi Nggong - Gendang Manggarai dalam Konteks Post-Agraris: Studi pada Komposisi Musik Barong Wae - Louise Marie Grignion de Monfort Mitak (Journal of Music Science, Technology, and Industry, 2026)
Purpose: This study aims to analyze the aesthetics of nggong–gendang sound in Manggarai within a post-agrarian context through the musical composition Barong Wae. The study is grounded in the transformation of musical practices originally embedded in agrarian ritual contexts into forms of artistic representation in musical composition. Employing a qualitative approach with a case study method, this research positions Barong Wae as the primary unit of analysis. Method: Data collection techniques include observation of musical structures, documentation of scores and recordings, and creative reflection within a practice-based research framework, where the compositional process is treated as analytical data. Result and Discussion: The findings reveal that the aesthetics of nggong–gendang sound undergo reconstruction through transformations in medium and musical structure, shifting from communal practices to Western ensemble instrumentation. This transformation is not merely technical but reflects a shift in function from participatory ritual engagement to artistic representation. Furthermore, the aesthetic experience changes from participatory and immersive to appreciative and reflective modes. Within a post-agrarian context, this reconstruction indicates that agrarian sound systems do not disappear but are recontextualized into new forms. Implication: This study contributes to contextual approaches in music aesthetics and offers creative strategies for developing musical practices rooted in local cultural traditions.